Preoperative vitamin D supplementation in patients with vitamin D deficiency undergoing total thyroidectomy - Ramouz, Ali; Hosseini, Mahdie; Hosseinzadeh, Seyedeh Shaghayegh; Rasihashemi, Seyed Ziaeddin (The American journal of the medical sciences, 2020)
Background - Transient hypocalcemia due to parathyroid gland or vessel manipulation is a common complication following thyroidectomy. Considering the role of 25-hydroxyvitamin D (25(OH)D) in calcium hemostasis, this study aimed to evaluate the effect of preoperative vitamin D supplementation on hypocalcemia incidence in thyroidectomy patients. - Methods - In this randomized clinical trial, 100 patients scheduled for total thyroidectomy and suffering from preoperative moderate or severe vitamin D deficiency were enrolled. Patients were randomly allocated to either study or control groups using the sealed envelope method. Patients in the study group received vitamin D3 50,000-unit pearl weekly for 4 weeks prior to the operation. The control group received placebo. Total and ionized serum calcium levels were checked before surgery, the day after surgery, and 2 weeks postoperatively. - Results - No significant difference was observed in terms of demographic data. During serial total calcium checks (5 episodes), total calcium levels changed significantly in patients who had received vitamin D supplements compared to the control group (P = 0.043). Symptomatic hypocalcemia incidence was significantly lower in patients supplemented with 25-hydroxyvitamin D (25(OH)D) (P = 0.04). Also, the requirement for intravenous calcium administration in order to treat the hypocalcemia symptoms was significantly lower in the study in comparison to the control group (P = 0.03). - Conclusions - Vitamin D supplementation in patients with vitamin D deficiency might lead to a lower incidence of early-onset symptomatic hypocalcemia; hence, requiring less calcium supplementation for the management of hypocalcemia.